Metabolic syndrome and incident depressive symptoms in young and middle-aged adults: A cohort study - Jeon, Sang Won; Lim, Se-Won; Shin, Dong-Won; Ryu, Seungho; Chang, Yoosoo; Kim, Sun-Young; Oh, Kang-Seob; Shin, Young-Chul; Kim, Young Hwan (Journal of affective disorders, 2019)
Highlights•We examined the prospective association between MetS and incident depression. •The incident depression revealed a U-shaped relationship with the number of MetS components. •The presence or absence of MetS was not significant in new-onset depression. •Out of MetS components, central obesity was the major driving factor of incident depression.